Optimal Location Determination For Boarding House Development In The Buffer Area Of The Sepuluh Nopember Institute Of Technology - Arsha Kusumandaru Q. Y.; Rivan Aji Wahyu Dyan Syafitri; Hilmy F; Naila Hafizhah I.; M. Albaqibillah (Jurnal Penataan Ruang, 2024)
The limited availability and consequent high cost of land have driven urban development to focus on vertical structures, such as student boarding houses. The selection of locations for these boarding houses is crucial, as it involves numerous subjective criteria. Public participation is vital in understanding preferences and ensuring the optimal choice of settlements. Moreover, stakeholders can use this information to enhance planning efforts for areas with high potential for boarding house development, significantly impacting urban infrastructure. Sepuluh Nopember Institute of Technology (ITS) significantly influences the growth of vertical buildings, including apartments and boarding houses in its surrounding areas. This study analyzes the optimal locations for boarding houses development in the ITS buffer zone using multi-criteria decision analysis. By adopting a bottom-up approach that incorporates student preferences, the study evaluates importance score and values from variables such as proximity to the campus center, supermarkets, food vendors, accessibility, and land price range. The findings indicate that Gebang Putih, Kejawan Tambak, and Upper Keputih are the most suitable locations for boarding houses development.